A once daily multi-unit system for the site-specific delivery of multiple drug regimens - Cooppan, Shivaan (My University, 2011)
Complex medication regimens have major implications on patient therapy. When we consider that these regimen therapies can also be further convoluted by co-morbidity, it is then seen as an essential opportunity to research possible solutions to alleviate such complications. Globally identified conditions such as the Human Immuno-deficiency Virus (HIV) and Tuberculosis (TB) are known to have such complications within their respective regimens. In many cases, the regimental therapies themselves are overbearing with high pill burdens having to be taken in segregated manners throughout the day. Within a standard TB regimen, isoniazid and rifampicin are seen to have a deleterious drug-drug interaction in which the bioavailability is compromised through formation of an insoluble complex. Despite this interaction, the 2 active drugs must be taken concurrently for successful TB therapy. No true solution exists as fixed dose combinations of isoniazid and rifampicin (Rifinah®) are still in production despite the detrimental interaction that impedes successful bioavailability. The once daily multi-unit drug delivery system (ODMUS) has the benefits of superseding the described problems and aiding in therapeutic outcomes. Preliminary studies utilized preliminary testing to ascertain the science surrounding the 2 components of the ODMUS, the memblet and the multiparticulate components. pH-sensitive polymers (Eudragit® L100-55 and E 100) were of critical importance to the success of the system and were individually manipulated for each component to produce a novel memblet and multiparticulate system through a unique salting out approach. Primary studies focused on drug release testing and drug entrapment for the multiparticulate component. Testing of the memblet system addressed dissolution and thermal analysis. Utilizing this data, a series of process variables were used to achieve an optimized formulation through a Box- Behnken statistical design. Optimized formulations used response testing to establish the optimal characteristics of both components. Multiparticulates achieved controlled release for 12 hours with an enhanced 71% drug entrapment efficiency. Memblet release profiles were confirmed over 2 hours with a maximal Tg of 56°C. Molecular modeling corroborated release understanding for both components. Surface area and porosity analysis, surface morphology, fourier transform infrared spectroscopy as well as thermal, rheological and mechanical analysis were additional tests undertaken on the optimized formulations. In vivo analysis was the final testing to verify validity of the ODMUS components and utilized a pig model for the investigation. UPLC blood analysis revealed increase blood levels of INH (CmaxINH= 0.0138ng/mL) and RIF (CmaxRIF= 0.052ng/mL) in relation to conventional dosage forms validating segregated site-specific release and increased bioavailability. Ideally, a segregated means of drug delivery throughout the gastrointestinal tract was achieved such that an enhanced bioavailability, a more controlled release and a simplified medication regimen was produced. This study aimed to achieve said goals through novel technique analysis, innovation and globally approved science to critically assess the success of the ODMUS as a potential means to reduce the complexities of medication regimen therapy.
Keywords: gastrointestinal tract; gastrointestinal tract; bioavailability; drug delivery; once dailymulti-unit system; multiple drug regimens